URBAN TREE PLANTING WITH NATIVE PLANTS IN 2013’S DROUGHT IN THE CITY OF SÃO JOSÉ DO SERIDÓ / RN - Medeiros, Josimar Araújo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
In Brazil, the rapid and unplanned growth of cities has caused neglect of tree composition of its roads and public places. With regard to afforestation by planting native species, can not perceive a focus for this issue in public policy attention. The study aimed to evaluate screen the survival of native species introduced for the purposes of urban forestry in the savanna biome plants, planted in the drought of 2013. Seedlings were provided by the Center for Seedling Production Xique-xique. The planting was done in February 2013 with the seedlings presented total height between 30cm and 60cm and being irrigated once a week with the amount of six liters of water for 12 months. Cajarana species (Spondias lutea) and ceriguela (Spondias purpurea) seedlings were produced by estarquia. 107 seedlings were planted belonging to 10 different species and six families. The cajarana (Spondias lutea) and tamarind (Tamarindus indica), respectively, 23.3% and 19.6% species were planted in greater numbers. The assessment carried out in April 2014, the survival rate was 100%. The research points to a pragmatic alternative is likely to be peaked in the process of afforestation of semiarid cities by the ability of living with the semiarides. No less important is the research with reference to low investment in planting and maintaining trees in urban waterways.